THE EFFECT OF PARTICIPATORY BUDGETING, INFORMATION ASYMETRICITY ON THE SLACK BUDGET AND THEIR IMPACT ON COMPANY PERFORMANCE LEVEL - Sabirin Sabirin (Accounting and Finance Studies, 2021)
This study aims to analyze the effect of participatory budgeting variables and information asymmetry on budgetary slack, and to analyze the effect of participatory budgeting and information asymmetry variables on company performance through budgetary slack. This research is causal (causal research). The study population is all offices of PT Angkasa Pura II (Persero) in Indonesia. The sample consists of a number of members selected from the population. The sampling technique used in this study is non probability sampling, that is total sampling. In this research a descriptive statistical analysis will be performed using path analysis. The results showed that Participatory Budgeting and Information Asymmetry had a significant positive effect on budgetary slack as well as on company performance. The Slcak budget has a significant positive effect on company performance. However, the Budgetary Slack in this research model did not succeed in mediating the relationship between Participatory Budgeting and Information Asymmetry on company performance.